Implementasi Hukum Tanah Wakaf dalam Konflik Pembangunan Masjid yang Berdekatan dengan Masjid Lainnya Perspektif Ibnu Taimiyyah (Studi Kasus di Desa Sei Lumut Kecamatan Panai Hilir Kabupaten Labuhanbatu) - Rizki, Ahmad; Rahman Harahap, Abd (UNES Law Review, 2023)
This research is a type of qualitative research located in Sei Lumut Village, Labuhan Batu Regency, with the research objectives being: 1) to find out how the waqf law is implemented on the activation of the benefits of waqaf land built by a mosque in Sei Lumut village; 2) to find out what Ibn Taimiyah's perspective was regarding the conflict over waqf land negotiations for the mosque built in Sei Lumut village. The results of the research show that the act of transferring the benefits of waqf land carried out by the waqif's children to become a mosque building is completely inconsistent with the provisions of Law no. 41 of 2004 concerning waqf and has violated articles 22, 23, 40, and article 41 and therefore his actions can also be subject to sanctions as stated in article 67 of Law no. 41 of 2004 concerning waqf. Meanwhile, according to Ibn Taimiyah's perspective, mosques built on waqf land are classified as dhiraran mosques built for the detriment of many people. They are permitted to be demolished to not cause obstacles among the people.